Unleashing entrepreneurial potential: Empowering social beneficiaries through the practice of developing marketing plans at Panti Sosial Bina Karya Harapan Jaya - Dida Nurhaida; Khomsiyah Khomsiyah; Yolanda Masnita (Community Empowerment, 2023)
Urbanization and welfare have become serious concerns in DKI Jakarta, especially with the increasing number of homeless people and beggars that have caused various social problems. The government has implemented comprehensive programs to address these issues, including a social rehabilitation program. Equipping social beneficiaries (WBS) with entrepreneurial skills is highly needed. This Community Service activity aims to unleashing entrepreneurial potential of WBS at the Panti Sosial Bina Karya (PSBK) Harapan Jaya, through the practice of developing marketing plans. Training was conducted through demonstrations, hands-on practice, and question-and-answer. This activity has successfully increased the knowledge of participants in developing simple yet effective marketing plans. A total of 85% of the participants stated that their understanding was better than before, and 80% of the participants felt capable of implementing it.